Фінансові аспекти відновлення конкурентоспроможності сфери гостинності України - Шматковська, Тетяна Олександрівна; Коробчук, Тетяна Іванівна (Луцький національний технічний університет, 2024)
У статті розглянуто фінансові аспекти відновлення конкурентоспроможності сфери гостинності України в контексті сучасних викликів та трансформацій національної економіки України. Розглянуто ключові фактори, що впливають на конкурентоспроможність галузі, такі як інвестиції в інфраструктуру, розвиток туристичної індустрії, фінансова підтримка малих та середніх підприємств, а також впровадження сучасних технологій у галузь гостинності. Досліджено функціональні стратегії фінансового управління, які можуть забезпечити під-вищення рівня конкурентоспроможності готельних комплексів, ресторанів, туристичних агентств та інших під-приємств галузі в сучасних умовах. Визначено необхідність залучення інвестицій та оптимізації фінансових процесів підприємств сфери гостинності, а також інші інструменти, спрямовані на підвищення їх рентабель-ності та конкурентоспроможності. Розглянуто перспективи та можливі шляхи розвитку галузі в умовах після-воєнного відновлення економіки України та зміни споживчих уподобань у даній сфері.
The purpose of the article is to study the financial aspects of restoring the competitiveness of the hospitality sector in Ukraine for the formation of financial management strategies aimed at the restoration and development of the relevant industry in the context of modern economic challenges and transformations. The relevance of the research lies in the fact that the field of hospitality in Ukraine faces significant challenges caused not only by economic and socio-cultural factors, but also by global trends caused by the destructive impact of the COVID-19 pandemic and Russian military aggression. Changes in consumer preferences, growing competition in the market, as well as the need to introduce new technologies and improve the quality of services in the hospitality industry make the financial aspect of restoring competitiveness an extremely urgent problem. Accordingly, the study of this issue is of great importance for the effective management and development of the hospitality sector in Ukraine, contributing to the increase of its internal stability and competitiveness at the international level. The research methodology is based on a comprehensive analysis of the industry's financial indicators, the use of economic models and forecasting methods. An analysis of scientific literature, statistical data, and empirical research was also used to obtain an objective view of the current state and prospects for the development of the hospitality industry in Ukraine. The obtained results demonstrate the key factors that influence the financial stability and competitiveness of the industry, including the level of investment, the efficiency of resource management, adaptation to changes in demand and the competitive environment, as well as the introduction of innovative technologies.
Keywords: конкурентоспроможність; сфера гостинності; відновлення конкурентоспроможності; готельне господарство; туристичний бізнес; фінансова стійкість; competitiveness; the field of hospitality; the restoration of competitiveness; hotel economy; tourism business; financial stability; 338.486.6:338.483.13